PI film conductive silver paste antenna with weldable electrode and preparation process thereof

By constructing conductive lines on a PI film and setting local openings, and filling them with palladium-containing solderable silver paste to form electrode pads, the problem of the conductive silver paste layer of the PI film antenna being difficult to wet with tin-based solder is solved. This improves solderability and connection reliability, reduces production costs and process complexity, and is suitable for mass production of flexible antennas.

CN121440133APending Publication Date: 2026-01-30FEIMA (JIANGSU) INTELLIGENT TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511632563.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-10
Publication Date
2026-01-30

AI Technical Summary

Technical Problem

In the prior art, the surface chemical properties of the conductive silver paste layer of PI film antennas are stable, making it difficult to form good wetting with tin-based solder. This results in the inability to achieve direct welding connection of electrode pads, increasing production processes and costs, and limiting the large-scale application of flexible antennas.

Method used

Conductive circuits are constructed on a PI film and local windows are set. Electrode pads are formed by filling with a solderable silver paste containing palladium, eliminating complex processes such as chemical gold plating. Plasma treatment is used to enhance the surface energy of the substrate. Combined with precise drilling and optimized printing parameters, electrode pads that can directly wet solder are formed, and a cross-linked protective coating is applied to the non-electrode areas.

Benefits of technology

It improves the solderability and connection reliability of electrode pads, reduces production costs and process complexity, enhances interface bonding and signal transmission stability, and improves the environmental tolerance and insulation safety of the antenna, making it suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121440133A_ABST
    Figure CN121440133A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of PI (polyimide) film printing conductive silver paste screen printing, and particularly relates to a PI film conductive silver paste antenna with a weldable electrode and a preparation process of the PI film conductive silver paste antenna with the weldable electrode. Complex procedures such as hot pressing of a protective film and chemical gold plating in a traditional process are omitted, and the production cost and period are remarkably reduced; meanwhile, the solderable silver paste has excellent solder wettability, and the bonding strength and long-term stability of a welding interface are improved by matching with a densified conductive structure after sintering; and the cross-linked protective coating covering the non-electrode area further enhances the resistance of the product to damp heat, bending and external pollution, and the technical effects of process simplification, reliable connection, good environmental tolerance and suitability for batch manufacturing are integrally realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of PI film printed conductive silver paste screen printing technology, specifically relating to a PI film conductive silver paste antenna with solderable electrodes and its fabrication process. Background Technology

[0002] In the field of flexible electronics, polyimide (PI) film is widely used as a substrate material for flexible antennas due to its excellent high-temperature resistance, mechanical strength, and insulation properties. Traditional PI film antennas often use copper foil etching to form conductive lines, but this method suffers from complex processes, significant environmental pollution, and low material utilization. In recent years, screen printing of conductive silver paste has gradually become an alternative. By directly printing silver paste onto the PI film to form antenna patterns, the process is simplified and environmental friendliness is improved.

[0003] However, a common problem in existing technologies is that the surface chemical properties of ordinary conductive silver paste layers are stable, making it difficult to form good wetting with tin-based solders, thus preventing direct soldering connections to the electrode pads. To solve this problem, additional surface treatment is usually required in the silver paste electrode area, such as hot-pressing a protective film before implementing a chemical gold plating process. Such processes not only increase production steps but also place higher demands on environmental control and equipment conditions, significantly increasing manufacturing costs and timelines, and limiting the large-scale application of flexible antennas. Summary of the Invention

[0004] The purpose of this invention is to provide a PI film conductive silver paste antenna with solderable electrodes and its fabrication process, which eliminates additional processing steps such as chemical gold plating, allowing the electrodes to be directly soldered to external components, effectively reducing process complexity and production costs, and solving the problems mentioned in the background art.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: a PI film conductive silver paste antenna with solderable electrodes, comprising: The substrate is a polyimide film whose surface is subjected to plasma treatment to form an activation layer. The polyimide film is printed with antenna conductive lines made of conductive silver paste. A circular through-hole is provided at the end of the antenna conductive line to expose the surface of the underlying polyimide film, forming an electrode window area; The electrode window area is filled with a palladium-containing solderable silver paste, which is then sintered to form an electrode pad that can directly wet the solder. The non-electrode areas are covered with a coating, which is then dried and cured at room temperature to form a cross-linked film.

[0006] On the other hand, this invention proposes a fabrication process for a PI film conductive silver paste antenna, comprising the following steps: A 50μm thick polyimide film was selected and wiped with anhydrous ethanol and treated with air plasma to increase the surface energy to over 45mN / m. The treated polyimide film was fixed on a vacuum adsorption platform, and conductive silver paste was printed using a 250-mesh stainless steel wire mesh under the conditions of a squeegee angle of 70°, a pressure of 0.35MPa, a speed of 20mm / s, and a distance of 1.8mm from the wire mesh to form the antenna conductive circuit. The printed polyimide film is baked in a step-by-step manner. First, it is pre-baked at 80℃ for 6 minutes to remove the solvent, and then kept at 150℃ for 18 minutes to decompose and cross-link the organic carrier, thereby achieving the initial curing of the conductive circuit. The CCD vision system is used to scan the end of the solidified conductive line, identify the center coordinates of the two predetermined electrode positions, and guide the CNC drilling device to move to the corresponding position.

[0007] Preferably, the two predetermined electrode positions include a first electrode and a second electrode; Using a 1.2 mm diameter diamond drill bit at the positions of the first and second electrodes, circular through holes were drilled at a rotation speed of 18,000 rpm and a feed rate of 0.08 mm / s to penetrate to the surface of the polyimide film.

[0008] Preferably, the center-to-center distance between the two holes of the first electrode and the second electrode is 10.0 mm. After completion, the residue inside and around the hole is cleaned with compressed air and isopropanol.

[0009] Preferably, the conductive silver paste is a solderable silver paste with a silver powder content of 75wt%, wherein the silver powder is a mixture of flake-like particles with an average particle size of 5μm and spherical nano-silver with an average particle size of 120nm in a mass ratio of 6:4, and 0.3% palladium is added as an active agent.

[0010] Preferably, the printed conductive silver paste comprises: The solderable silver paste was placed in a planetary mixer and stirred for 12 minutes at 300 rpm revolution and 900 rpm rotation. Then it was printed onto the electrode window area using an 80-mesh stainless steel screen.

[0011] Preferably, the printed conductive silver paste further includes: During printing, the squeegee angle is set to 65°, the pressure is 0.45MPa, the speed is 15mm / s, and a unidirectional double printing method is used. After each printing, the paper is left to stand for 3 minutes to obtain a pad structure with a total wet film thickness of about 30μm.

[0012] Preferably, the printed conductive silver paste further includes: The printed polyimide film is placed in a nitrogen-protected oven with an oxygen content of less than 10 ppm. It is first pre-baked at 80°C for 8 minutes to remove the solvent, and then heated to 180°C at a rate of 4°C / min and held for 35 minutes to promote the sintering and densification of silver particles.

[0013] Preferably, after the silver particles are sintered and densified, tin-lead eutectic solder heated to 220°C is applied to the electrode pads, and it is observed whether it rapidly spreads within 0.5 seconds to form a smooth solder joint with a contact angle of less than 45°.

[0014] Preferably, an acrylic protective coating with a solid content of 35% and a viscosity of 2500 cP is uniformly coated on the non-electrode area using a slit-type coating head, with a thickness of 12 μm. Then, it is dried at 70°C for 10 minutes and cured at room temperature for 2 hours to complete the encapsulation.

[0015] Technical effects and advantages of the present invention: The PI film conductive silver paste antenna with solderable electrodes proposed in this invention and its fabrication process have the following advantages compared with the prior art: This invention constructs conductive lines on a polyimide film and sets local windows, filling the exposed areas with palladium-containing solderable silver paste to form electrode pads. This eliminates the complex processes of hot-pressing protective films and chemical gold plating in traditional processes, significantly reducing production costs and time. At the same time, the solderable silver paste has excellent solder wettability, which, combined with the dense conductive structure after sintering, improves the bonding strength and long-term stability of the welding interface. The cross-linked protective coating covering the non-electrode areas further enhances the product's resistance to humidity, bending, and external pollution. Overall, it achieves the technical effects of simplified process, reliable connection, good environmental tolerance, and suitability for mass production. Attached Figure Description

[0016] Figure 1 This is a schematic diagram of the structure of the PI film conductive silver paste antenna of the present invention; Figure 2 This is a process flow diagram for fabricating the PI film conductive silver paste antenna of the present invention.

[0017] In the diagram: 1. Conductive silver paste; 2. Polyimide film; 3. Through-hole; 4. Electrode pad. Detailed Implementation

[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The specific embodiments described herein are merely used to explain the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] Example 1 This invention provides, for example Figure 1 The antenna shown is a PI film conductive silver paste antenna with solderable electrodes. The antenna uses a polyimide film as a substrate and forms a conductive circuit structure and electrode pads that can be directly used for soldering by screen printing. This eliminates the complex and costly surface treatment processes such as hot pressing protective film and chemical gold plating in traditional processes, and realizes an integrated manufacturing path from material selection, pattern printing to functional electrode construction.

[0020] The core materials used in this embodiment include: polyimide (PI) film as a flexible substrate, which has excellent temperature resistance, mechanical strength and insulation properties; conductive silver paste used to construct the conductive path of the antenna body; and solderable silver paste used for printing in the electrode area, which has good wettability and metal bonding ability.

[0021] In this embodiment, the PI film conductive silver paste antenna specifically includes: a substrate, which is a polyimide film 2, the surface of which is plasma treated to form an activation layer; an antenna conductive line composed of conductive silver paste 1 is printed on the polyimide film; a circular through hole 3 is provided at the end of the antenna conductive line to expose the surface of the underlying polyimide film and form an electrode window area; a solderable silver paste containing palladium is filled in the electrode window area, and the solderable silver paste is sintered to form an electrode pad 4 that can directly wet solder; wherein, the non-electrode area is covered with a coating, and the coating is dried and cured at room temperature to crosslink into a film.

[0022] By adopting the above structure, the problem of direct soldering of ordinary conductive silver paste is effectively solved, and the solderability and connection reliability of electrode pads are improved. Additional surface treatment processes such as chemical gold plating are eliminated, reducing production costs and process complexity. The combination of local windowing in the electrode area and solderable silver paste enhances the interface bonding force and signal transmission stability. At the same time, the introduction of the protective coating significantly improves the environmental durability and insulation safety of the antenna under humid heat, bending and long-term use conditions. The overall structure is more conducive to achieving efficient, stable and large-scale flexible electronic manufacturing.

[0023] The above-mentioned fabrication process of a PI film conductive silver paste antenna, such as... Figure 2 As shown, it includes the following steps: A 50μm thick polyimide film was selected and wiped with anhydrous ethanol and treated with air plasma to increase its surface energy to over 45mN / m. By increasing the surface energy of the polyimide film, the wettability and adhesion of the substrate to the conductive silver paste were significantly enhanced, effectively preventing edge lifting or local peeling of the silver paste layer after printing. This provided a good interface foundation for the stable construction of subsequent multilayer structures, while reducing defects such as broken lines and incomplete printing caused by poor adhesion, thus improving product yield and long-term reliability.

[0024] The treated polyimide film was fixed on a vacuum adsorption platform, and conductive silver paste was printed using a 250-mesh stainless steel wire mesh at a 70° squeegee angle, 0.35 MPa pressure, 20 mm / s speed, and a 1.8 mm distance from the wire mesh to form the antenna conductive circuit. By controlling the printing parameters, the uniform transfer of conductive silver paste on the substrate and the fidelity of the pattern were ensured, effectively avoiding defects such as missing prints, broken lines, or edge burrs, and achieving stable replication of fine circuits. The vacuum adsorption fixing method ensured the flatness and displacement of the film during the printing process, improved the consistency and alignment accuracy of multiple batches of production, and laid the foundation for the stability of subsequent electrode processing and overall electrical performance.

[0025] The printed polyimide film is subjected to a stepped baking process. First, it is pre-baked at 80℃ for 6 minutes to remove the solvent, and then held at 150℃ for 18 minutes to decompose and crosslink the organic carrier, achieving preliminary curing of the conductive circuit. Through staged temperature-controlled curing, the solvent is steadily evaporated and the organic components are decomposed in an orderly manner, effectively avoiding defects such as blistering, cracking, or internal pores caused by rapid heating. This ensures that the silver particles are gradually and densely arranged to form a continuous conductive network. This curing process improves the mechanical strength and adhesion stability of the silver paste layer, providing a reliable structural foundation for subsequent processing steps, while ensuring the low resistivity and long-term reliability of the conductive circuit.

[0026] A CCD vision system is used to scan the ends of the solidified conductive lines, identify the center coordinates of two predetermined electrode positions, and guide a CNC drilling device to the corresponding positions. Specifically, the two predetermined electrode positions include a first electrode and a second electrode. At the positions of the first and second electrodes, a 1.2 mm diameter diamond drill bit is used to drill circular through holes at a rotation speed of 18,000 rpm and a feed rate of 0.08 mm / s, penetrating to the surface of the polyimide film.

[0027] Furthermore, the center-to-center distance between the two holes of the first and second electrodes is 10.0 mm. After completion, the holes and surrounding residues are cleaned with compressed air and isopropanol.

[0028] The coordinated use of high-precision visual positioning and CNC machining ensures the accuracy and repeatability of electrode opening positions, effectively avoiding connection failures or assembly difficulties caused by misalignment. The use of controllable parameter mechanical drilling enables precise micro-hole forming with smooth hole walls that do not damage surrounding conductive lines, ensuring the integrity of the underlying substrate. Thorough removal of residues inside and around the holes eliminates contaminants that could affect interlayer bonding, providing a clean and reliable contact surface for subsequent solderable silver paste filling and interface bonding, significantly improving the electrical connection quality and structural stability of the electrode area.

[0029] The conductive silver paste mentioned above has a silver powder content of 75wt% and is a solderable silver paste. The silver powder is made by mixing flake-shaped particles with an average particle size of 5μm and spherical nano-silver with an average particle size of 120nm in a mass ratio of 6:4, and 0.3% palladium is added as an active agent.

[0030] The process of printing conductive silver paste includes: placing solderable silver paste in a planetary mixer and stirring for 12 minutes at 300 rpm revolution and 900 rpm rotation; then printing it onto the electrode window area using an 80-mesh stainless steel screen. During printing, the squeegee angle is set to 65°, the pressure is 0.45 MPa, the speed is 15 mm / s, and a unidirectional double-printing method is used. After each printing, the film is allowed to stand for 3 minutes to obtain a pad structure with a total wet film thickness of approximately 30 μm. The printed polyimide film is then placed in a nitrogen-protected oven with an oxygen content of less than 10 ppm. It is first pre-baked at 80°C for 8 minutes to remove solvent, then heated to 180°C at a rate of 4°C / min and held for 35 minutes to promote the sintering and densification of the silver particles. After the silver particles are sintered and densified, tin-lead eutectic solder heated to 220°C is applied to the electrode pads, and it is observed whether it rapidly spreads within 0.5 seconds to form smooth solder joints with a contact angle of less than 45°.

[0031] The silver powder employs a composite ratio of flake and spherical nanoparticles, and the introduction of palladium significantly promotes effective interparticle bonding and interface activation during sintering, facilitating the formation of a dense, continuous conductive network. Simultaneously, it lowers the sintering temperature and enhances the metallurgical reactivity with the solder. Planetary stirring ensures uniform dispersion of the slurry, preventing agglomeration and guaranteeing the uniformity of the printed layer. Optimized printing parameters and a dual-printing process work synergistically to achieve a sufficiently thick pad structure, providing ample material support and heat capacity for soldering. Gradient-temperature sintering in a low-oxygen, nitrogen-filled environment effectively inhibits silver particle oxidation, ensuring surface cleanliness and activity. This results in excellent solder wetting properties on the electrode pads, enabling rapid spreading and stable connection with a low contact angle, significantly improving soldering reliability and interfacial bonding strength.

[0032] Specifically, an acrylic protective coating with a solid content of 35% and a viscosity of 2500 cP is uniformly applied to the non-electrode area using a slit-type coating head, with a thickness of 12 μm. The coating is then dried at 70°C for 10 minutes and cured at room temperature for 2 hours to complete the encapsulation.

[0033] The protective coating forms a continuous and dense insulating barrier in non-electrode areas, effectively blocking moisture, dust, and external contaminants from corroding the conductive lines and preventing oxidation, leakage, or short circuits during long-term use. Its moderately cross-linked structure maintains flexibility while possessing good adhesion and scratch resistance, adapting to the deformation requirements of PI film in dynamic applications such as bending and winding. Precisely controlled coating thickness avoids interference with the electrode area, ensuring that the welding function is not affected. The low-temperature drying and natural curing process balances efficiency and material stability, reducing the impact of thermal stress on the formed circuit, and comprehensively improving the electrical safety and service life of the antenna in complex environments.

[0034] Example 2 This embodiment proposes a fabrication process for a PI film conductive silver paste antenna, which further optimizes the fabrication process in Example 1 to ensure the fabrication quality of the PI film conductive silver paste antenna. The process includes the following steps: Step 1: Selection and Surface Pretreatment of PI Film Substrate Because PI film itself has a strong surface inertness, it is not conducive to ink adhesion. Without effective pretreatment, the silver paste layer will experience edge lifting, local peeling, or even complete detachment after drying and curing. Therefore, it is necessary to systematically clean and activate the PI film to improve its interfacial bonding ability with the silver paste, laying a solid foundation for subsequent multi-layer printing.

[0035] 1.1 A 50μm thick double-sided smooth polyimide (PI) film roll was selected, with a tensile strength of not less than 200MPa, no significant deformation after 100 hours of continuous operation at 250℃, a dielectric constant of 3.4±0.2 (at 1MHz), and a volume resistivity greater than [missing value]. This specification of PI film maintains sufficient mechanical support while possessing excellent flexibility, making it suitable for applications involving repeated bending, such as flexible antenna components in wearable devices. As the load-bearing platform for the entire antenna structure, the physical dimensional stability of this PI film directly affects the final product's graphic accuracy and electrical consistency.

[0036] 1.2 Cut the PI film into single sheets of 200mm × 300mm according to the designed length, and fix them on the vacuum adsorption platform of the clean bench to ensure they remain flat and wrinkle-free throughout the process. This fixing prevents uneven processing or edge contamination caused by film movement during subsequent cleaning and activation, and also provides a reference plane for the positioning of subsequent automated printing equipment. The flatness deviation should be controlled to no more than 0.1mm per 100mm to avoid differences in printing thickness due to substrate undulations.

[0037] 1.3 The PI film surface is wiped twice with anhydrous ethanol. Each time, a clean cotton cloth soaked in an appropriate amount of ethanol is slid along the same direction at a uniform speed to remove residual release agent, grease, and micro-dust particles. Ethanol evaporates quickly and has no swelling effect on the PI film, effectively dissolving non-polar contaminants without damaging the substrate structure. This cleaning process significantly reduces the interference of surface impurities on the wetting behavior of the silver paste, allowing the silver paste to spread more evenly on the substrate and reducing the probability of defects such as incomplete printing and broken lines.

[0038] 1.4 After solvent cleaning, the PI film is placed in a plasma treatment chamber using air as the working gas and treated for 3 minutes at 80W power and 80Pa pressure, increasing the surface energy from the original 32mN / m to over 45mN / m. High-energy particles in the plasma bombard the PI film surface, breaking CH and CO bonds and generating numerous oxygen-containing polar groups (such as -COOH and -OH), enhancing the surface's hydrophilicity and chemical activity. This activation effect greatly promotes the molecular-level interaction between the organic carrier and the substrate in the silver paste, thus forming a more robust initial adhesion layer in subsequent printing processes, laying the foundation for the long-term stability of the entire conductive structure.

[0039] Step 2: Preparation of conductive silver paste and preparation of screen printing plate After pretreatment of the PI film substrate, the next step is to prepare for the printing of conductive lines on the antenna body. The core task at this stage is to prepare conductive silver paste suitable for the printing process and to create a matching screen template to ensure the accuracy and consistency of pattern transfer. The conductive silver paste not only needs to have good conductivity but also needs to exhibit suitable rheological properties during the printing process so that it can pass smoothly through the mesh and be accurately deposited on the target area under the push of the squeegee.

[0040] 2.1 A commercially available low-temperature curing conductive silver paste with a total silver powder content of 63 wt% was used. The silver powder was composed of flake-shaped silver microparticles (average particle size 3 μm) and spherical silver nanoparticles (average particle size 80 nm) mixed at a mass ratio of 7:3. The flake-shaped particles facilitate the formation of an overlapping conductive network, reducing sheet resistance; the spherical particles fill the gaps, improving the fluidity of the paste. The synergistic effect of the two can achieve a dense conductive layer at a relatively low sintering temperature. The remaining components of the silver paste are organic carriers (terpineol, ethyl cellulose, etc.) and trace dispersants, which together maintain the stable suspension state of the paste.

[0041] 2.2 Place the above silver paste in a vacuum mixer and stir for 15 minutes at 400 rpm and a vacuum of 0.09 MPa to remove air bubbles introduced during transportation or storage and to fully homogenize the components. The presence of air bubbles can cause voids or breaks in the printed lines, affecting the continuity of conductivity; homogenization ensures the uniform distribution of silver powder in the paste, avoiding local enrichment or depletion, thereby ensuring the consistency of the printed layer thickness and the stability of the resistance value.

[0042] 2.3 A 250-mesh stainless steel wire mesh was selected as the printing template for the conductive silver paste. The wire diameter was 32μm, the aperture ratio was 38%, and the tension was controlled at... High-mesh-count screen printing achieves higher graphic resolution, suitable for reproducing fine lines. A two-component diazo-type photosensitive emulsion is uniformly coated onto the screen using a photosensitive emulsion coating machine, with the wet film thickness controlled at 15μm, followed by drying at 40℃ for 10 minutes. This screen structure determines the final geometry of the conductive lines; its tension uniformity and emulsion thickness directly affect the edge sharpness and thickness consistency of the printed lines.

[0043] 2.4 Fabricate a positive film according to the antenna design drawings, adhere it tightly to the dried photosensitive emulsion layer, and expose it for 60 seconds using a 365nm ultraviolet light source. The exposure energy is [missing information]. After exposure, the image is developed by spraying with deionized water. The photosensitive emulsion in the unexposed areas swells and peels off, forming through-hole areas corresponding to the antenna pattern. The image is then dried with hot air to complete the screen printing. This screen accurately reproduces the serpentine trace structure of the antenna, with a line width of 200μm and a line spacing of 300μm, providing a graphic template for precise printing in the next step.

[0044] Step 3: Printing and initial curing of conductive silver paste After the silver paste preparation and screen printing plate preparation are completed, the actual printing stage begins. This step involves precisely transferring the conductive silver paste to the surface of the activated PI film using screen printing technology, forming the main conductive path of the antenna. The printing quality directly determines the electrical performance and structural integrity of the antenna; therefore, printing parameters must be strictly controlled to ensure uniform paste transfer and a complete and flawless pattern.

[0045] 3.1 Install the prepared screen printing plate from step two onto a semi-automatic flatbed screen printing machine, and adjust the distance between the screen and the PI film processed in step one to 1.8mm. If this distance is too small, the screen may stick to the substrate, causing stringing or pattern deformation; if it is too large, it will affect the paste transfer efficiency, resulting in insufficient filling. A precision adjustment mechanism ensures consistent screen height throughout the printing area, providing mechanical assurance for uniform printing.

[0046] 3.2 The squeegee angle is set to 70°, the blade straightness error to be less than 0.02mm, the applied pressure to 0.35MPa, and the printing speed to 20mm / s. Under this parameter combination, the silver paste undergoes thixotropic flow under the shearing action of the squeegee, its viscosity decreases, and it smoothly passes through the mesh and deposits on the PI film surface. The squeegee angle affects the balance between the paste propulsion force and the backflow resistance, the pressure determines the filling density, and the speed affects the residence time and screen removal effect. The three factors work together to achieve the best printing quality.

[0047] 3.3 The printing process is initiated. The squeegee pushes the silver paste along the screen surface, allowing it to fall through the mesh into the corresponding area of ​​the PI film, forming a continuous wet conductive line. After printing, the screen is slowly raised to avoid burrs or breakage at the line edges caused by negative pressure suction due to rapid separation. The printed pattern is a symmetrical serpentine structure with a total length of approximately 280mm, used for UHF band wireless communication. Its geometry has been simulated and optimized to match the impedance characteristics at the target frequency.

[0048] 3.4 Immediately after printing, the PI film is placed in a stepped oven for drying: First, it is pre-dried at 80℃ for 6 minutes to gradually evaporate the volatile solvents (mainly terpineol) in the paste, preventing surface blistering or cracking caused by sudden high-temperature heating; then, the temperature is raised to 150℃ and held for 18 minutes to promote the decomposition of the organic carrier and its cross-linking reaction with the silver particles, initially forming a conductive network. Although not fully densified at this stage, it already possesses a certain mechanical strength and can withstand subsequent processing operations without damage.

[0049] Printing thickness The following empirical relationship exists between screen parameters and the parameters: ; in: The wet film printing thickness (μm) is the thickness of the film. The wire diameter is (μm). The screen opening ratio is dimensionless. The process coefficient (taken as 0.6-0.8) comprehensively reflects the influence of scraper pressure, speed and slurry rheological properties.

[0050] In this embodiment, ,Pick Substituting, we get: ; The result is close to the target thickness range (8–15 μm), indicating that the selected parameter combination is reasonable and can achieve the expected conductive layer thickness.

[0051] Step 4: Positioning and windowing of the electrode pad area After the conductive silver paste layer has undergone initial curing, solderable electrodes need to be fabricated at designated locations at its ends to enable electrical connections with external components or wiring harnesses. Since the solderable silver paste only needs to be printed in localized areas, the electrode areas must be precisely positioned and exposed on the formed conductive layer; this process is called "windowing." This operation requires not only accurate positioning but also avoidance of damage to the underlying conductive structure.

[0052] 4.1 A high-precision CCD vision system is used to automatically align and scan the PI film printed and baked in step three, identifying the center coordinates of the two predetermined electrode positions at the end of the conductive lines, with the positioning error controlled within ±15μm. The vision system calculates the offset by comparing the edge feature points of the preset template and the actual graphic, and feeds it back to the motion platform to ensure that the subsequent processing reference is strictly aligned with the design drawings.

[0053] 4.2 Based on the acquired coordinate information, the CNC drilling device is moved to above the first electrode position. A 1.2mm diameter micro diamond drill bit is used to drill a circular through-hole in the conductive silver paste layer at a rotation speed of 18000rpm and a feed rate of 0.08mm / s, penetrating to the surface of the underlying PI film. This hole forms the initial outline of the electrode pad, and its size is slightly larger than the final pad area, reserving space for subsequent filling with solderable silver paste.

[0054] 4.3 Repeat the above steps to create a hole of the same diameter at the second electrode location. The center-to-center distance between the two holes should be 10.0 mm, meeting the pin spacing requirements of standard connectors. The dual-electrode design supports differential signal transmission or power / ground connection, enhancing the antenna's anti-interference capability in complex electromagnetic environments. After creating the hole, check that the hole walls are smooth and free of carbon residue to ensure that the underlying PI film has not been damaged by heat.

[0055] 4.4 Use compressed air and a brush to remove silver filings and dust from inside and around the holes. Then, gently wipe the edges of the holes with isopropyl alcohol swabs to remove any tiny contaminants that may affect interlayer bonding. This cleaning action prevents foreign matter from forming a weak interface between the old and new silver paste layers, thereby ensuring the quality of electrical contact and mechanical bonding strength between the subsequent solderable silver paste and the underlying conductive layer. At this point, the electrode area is ready, creating the necessary physical conditions for the next stage of solderable silver paste printing.

[0056] Step 5: Preparation of solderable silver paste and fabrication of printing screen After completing the positioning and windowing of the electrode pad areas, the crucial stage of functional electrode construction begins. The core of this step is selecting a solderable silver paste with excellent wettability and metal bonding capabilities, and precisely printing it onto the exposed electrode windows from the previous steps using a specialized screen printing stencil, forming a conductive contact surface suitable for subsequent direct soldering. Because this silver paste needs to achieve a reliable metallurgical bond with tin-based solder, copper leads, or surface-mount component pins, its formulation and printing process must meet specific interface compatibility requirements.

[0057] 5.1 A low-temperature curable solderable silver paste with a silver powder content of 75wt% was prepared. The silver powder consisted of flake-like particles with an average particle size of 5μm and spherical nano-silver with an average particle size of 120nm, mixed at a mass ratio of 6:4. Compared to conductive silver paste, this paste additionally added 0.3% palladium as an active agent. Palladium can reduce the activation energy of the reaction between the tin solder and the silver interface, promote the formation of Sn-Ag intermetallic compounds (IMC), thereby improving the bonding strength and thermal fatigue resistance of the solder joint. The organic carrier adopted was a modified terpineol system, which has better residual carbon control capabilities and decomposes completely during the curing process, reducing the impact of insulating residues on the soldering quality.

[0058] 5.2 Place the above-mentioned solderable silver paste in a planetary mixer and stir for 12 minutes at a revolution speed of 300 rpm and a rotation speed of 900 rpm to ensure that the silver powder is uniformly dispersed in the carrier under high shear force and to avoid agglomeration. This biaxial stirring method can effectively break the van der Waals force aggregation between particles, so that the paste as a whole exhibits stable pseudoplastic fluid characteristics. That is, the viscosity decreases under the push of the doctor blade to facilitate flow, and the original structure is quickly restored after the shearing stops, preventing the pattern from collapsing after printing.

[0059] 5.3 An 80-mesh stainless steel wire mesh was selected for printing solderable silver paste. The wire diameter was 50μm, the aperture ratio was 48%, and the tension was set to... Low-mesh screens allow for larger volumes of paste to pass through, suitable for thick-film printing needs, ensuring that the electrode pads have sufficient material thickness to withstand the thermal stress and mechanical tension during the soldering process. A single-component diazo photosensitive emulsion is uniformly coated onto the screen using a squeegee applicator, with the wet film thickness controlled at 18 μm, and then dried at 45°C for 15 minutes to form a photosensitive layer suitable for large-aperture pattern transfer.

[0060] 5.4 Based on the electrode pad design dimensions (1.4mm diameter circle), create an independent film pattern, tightly adhere it to the dried photosensitive adhesive layer, and expose it using a 365nm ultraviolet light source for 70 seconds at an exposure energy of 90mJ / cm². 2After development, circular through-holes corresponding to the window positions are obtained, and then the screen is fixed by drying with hot air at 100℃ for 10 minutes. This screen is specially used for local thickening printing in the electrode area. Its graphic size is slightly larger than the bottom opening, ensuring that the solderable silver paste completely covers the exposed area and slightly extends to the edge of the surrounding conductive layer, forming a stepped transition structure and enhancing the reliability of interlayer connection.

[0061] Step Six: Printing and Secondary Curing of Solderable Silver Paste After completing the fabrication of the specialized screen printing plate, solderable silver paste is precisely printed onto the electrode windowed areas prepared in the previous steps, and then subjected to high-temperature curing to form a robust electromechanical integrated structure with the underlying conductive lines. This step not only determines the physical integrity of the electrode itself, but also directly affects the solderability and long-term service stability of the final product.

[0062] 6.1 Mount the solderable silver paste stencil prepared in step five onto the same screen printing equipment, adjusting the distance between it and the PI film to 2.2 mm, which is slightly larger than when printing conductive silver paste, to accommodate thicker screen wire diameters and reduce the risk of clogging. Strictly align the center of the stencil pattern with the electrode coordinates determined in step four, using a vision system for fine-tuning to ensure that the printing position deviation is less than ±20 μm, guaranteeing compatibility in subsequent assembly.

[0063] 6.2 The squeegee angle was set to 65°, the applied pressure to 0.45 MPa, and the printing speed to 15 mm / s. Under this parameter combination, the high-viscosity solderable silver paste fully filled the mesh openings under strong shear and was completely transferred to the open area upon screen removal. Since the target pads were isolated island structures, a unidirectional double-printing method was adopted: after the first print, the paste was allowed to settle for 3 minutes, and then the second print was applied on top to achieve a higher deposition thickness; the target wet film thickness was approximately 30 μm.

[0064] 6.3 After printing, observe the surface morphology of the pads. They should be smooth and raised, without pinholes, cracks, or edge shrinkage. If insufficient filling is found in some areas, reprinting can be done once in the same process, but no more than three times, to prevent solvent accumulation from causing interlayer delamination. Both electrode pads should be completed simultaneously using the same process to ensure consistency in height, shape, and composition, avoiding soldering misalignment or stress concentration caused by asymmetry.

[0065] 6.4 The printed PI film is then placed in a nitrogen-protected oven for stepped temperature curing: First, it is pre-baked at 80℃ for 8 minutes to remove the solvent, then heated to 180℃ at a rate of 4℃ / min and held for 35 minutes to completely decompose the organic carrier and sinter and densify the silver particles, forming a continuous conductor. A nitrogen atmosphere (oxygen content <10ppm) prevents silver oxidation at high temperatures, maintains surface cleanliness, and provides an active metal surface for subsequent soldering. Through this process, the bottom conductive silver paste and the upper solderable silver paste achieve particle-level interpenetration and fusion at the interface, forming a unified conductive path with good resistance continuity.

[0066] Step 7: Welding performance verification and connection strength assessment After all printing and curing processes are completed, the prepared electrode pads must undergo actual welding tests to verify their reliable connection capabilities. This step simulates welding behavior in real-world application scenarios to examine solder wetting effects, interfacial bonding strength, and electrical conductivity quality, ensuring stable operation of the product after it is put into use.

[0067] 7.1 Take a standard tin-lead eutectic solder (Sn63 / Pb37, melting point 183℃) and heat it to a molten state at 220℃. Using a fine-diameter soldering iron tip, dip an appropriate amount of solder into the surface of the solderable silver paste pad formed in step six and gently touch it to observe the solder spread. Ideally, the molten solder should rapidly wet the entire pad area within 0.5 seconds, forming a smooth, continuous crescent-shaped solder joint with a contact angle of less than 45°, indicating that the silver paste surface has good solder affinity and is not contaminated by organic residues.

[0068] 7.2 After the solder joint has cooled and solidified, use a precision push-pull force tester equipped with a cylindrical probe (1.0 mm in diameter) to apply a uniform tensile force at a speed of 0.8 mm / min to the top of the solder joint, and record the maximum load value until the solder joint breaks or detaches from the substrate. This value reflects the overall mechanical strength of the solder joint. If the breakage occurs inside the solder rather than at the interface, it indicates that a good metallurgical bond has been formed between the silver paste and the solder; if the breakage occurs at the interface between the silver paste and PI, it indicates insufficient adhesion.

[0069] 7.3 Solder a tinned copper lead (0.5mm in diameter) to another pad, with a solder joint length of approximately 2mm. After cooling, connect it to a DC power supply circuit and apply a 5V voltage. Measure the voltage drop between the antenna input terminal and the lead end, and calculate the equivalent resistance using the known current value. Under normal circumstances, this resistance increment should not exceed 15% of the original conductive line resistance, indicating that the contact impedance introduced by the electrode is extremely small and no significant power loss node is formed.

[0070] 7.4 Perform thermal shock cycling tests on the welded samples: Place them in a temperature-varying chamber and subject them to alternating temperatures from -40℃ to 125℃, maintaining each temperature for 15 minutes, for a total of 300 cycles. After the tests, re-inspect the appearance and electrical continuity of the weld joints. If no cracks, desoldering, or sudden changes in resistance are observed, it proves that the constructed electrode structure has the ability to withstand complex environmental changes and meets the basic durability requirements for industrial applications.

[0071] In addition, in step seven, the push-pull force of the solder joint Its shear strength The relationship can be expressed by the following formula: ; in This refers to the effective load-bearing area of ​​the weld joint. For diameter... The circular pads include: ; If the maximum thrust is measured Then the average shear strength can be estimated as: ; This value is higher than the minimum requirement for general electronic connectors (≥8MPa), indicating that the solder joint has sufficient mechanical load-bearing capacity.

[0072] Step 8: Overall structural packaging and shipment inspection After confirming that the electrodes have good solderability, the final step is to perform protective encapsulation and comprehensive quality inspection on the finished antenna to improve its resistance to damage during transportation, storage and installation, and to ensure that every product leaving the factory meets the design specifications.

[0073] 8.1 A transparent, flexible acrylic protective coating with a solid content of 35% and a viscosity of 2500 cP was prepared. A 12 μm thick insulating film was uniformly coated onto the non-electrode area of ​​the PI film using a slit-type coating head, avoiding the two soldered or to-be-soldered electrode pads to prevent the coating from obstructing subsequent connections. This coating exhibits excellent moisture-proof, dust-proof, and scratch-resistant properties, while maintaining the flexibility of the antenna body; a bending radius of up to 5 mm can be achieved without cracking.

[0074] 8.2 After coating, dry at 70℃ for 10 minutes to achieve initial cross-linking, then allow to stand at room temperature for 2 hours to complete natural curing. During this process, the coating molecular chains further cross-link, forming a three-dimensional network structure, enhancing its mechanical strength and chemical stability. The dried coating surface should be smooth and transparent, free of bubbles, orange peel, or embedded impurities, and the conductive lines underneath should still be clearly visible through the coating.

[0075] 8.3 Use automated optical inspection equipment to perform a full-width scan of the entire PI film, focusing on checking for defects such as broken lines, short circuits, missing prints, or burrs in the conductive lines, whether the electrode pads are complete, symmetrical, and accurately positioned, and whether the protective coating covers the correct area. The system automatically marks abnormal points according to preset rules, and manual review is required to determine whether rework or scrap is necessary, ensuring that defective products do not flow into the next stage.

[0076] 8.4 Stack qualified products neatly in groups of 10, pack them into anti-static aluminum foil bags, seal them, and affix labels indicating the production batch, quantity, date, and key parameters (such as applicable frequency range and nominal impedance value). After placing the packaging units in turnover boxes, transport them to the warehouse area to await shipment. This completes the manufacturing process for a PI film conductive silver paste antenna with solderable electrodes. The product can be directly used in wireless module assembly, smart tag integration, or IoT terminal devices without additional electroplating or surface treatment processes.

[0077] In summary, this embodiment, by combining material properties, process parameters, and physical laws, successfully achieved the integrated manufacturing of PI film conductive silver paste antennas that can be directly soldered without chemical gold plating. The entire process simplifies traditional procedures, reduces energy consumption and environmental burden, and improves production efficiency and product consistency, making it suitable for the industrial production of large-scale flexible electronic devices.

[0078] Finally, it should be noted that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A PI film conductive silver paste antenna with solderable electrodes, characterized in that, The application relates to a polyimide substrate with an electrode pad structure. The application comprises: a substrate, which is a polyimide film with an activated layer formed on the surface after plasma treatment; an antenna conductive circuit composed of conductive silver paste is printed on the polyimide film; a circular through hole is arranged at the end of the antenna conductive circuit to expose the surface of the underlying polyimide film and form an electrode window area; a solderable silver paste containing palladium elements is filled in the electrode window area, and the solderable silver paste forms an electrode pad which can be directly wetted by solder after sintering; 2. A manufacturing process for manufacturing the PI film conductive silver paste antenna according to claim 1, characterized in that, wherein a coating is covered on the non-electrode area, and the coating is crosslinked into a film after drying and room temperature curing. The application comprises the following steps: select a polyimide film with a thickness of 50 mu m, and perform ethanol wiping and air plasma treatment on the polyimide film to improve the surface energy to above 45 mN / m; fix the treated polyimide film on a vacuum adsorption platform, print the conductive silver paste on the polyimide film to form an antenna conductive circuit under the conditions of a 250-mesh stainless steel wire screen, a scraper angle of 70 DEG, a pressure of 0.35 MPa, a speed of 20 mm / s and a distance of 1.8 mm from the screen; perform step-by-step baking on the printed polyimide film, first pre-bake at 80 DEG C for 6 minutes to remove the solvent, and then heat at 150 DEG C for 18 minutes to decompose and crosslink the organic carrier and realize preliminary solidification of the conductive circuit; 3. The manufacturing process of claim 2, wherein, scan the end of the solidified conductive circuit by using a CCD vision system, identify the center coordinates of two predetermined electrode positions, and guide a numerical control drilling device to move to the corresponding positions. The two predetermined electrode positions comprise a first electrode and a second electrode; 4. The manufacturing process of claim 3, wherein, use a diamond drill bit with a diameter of 1.2 mm to drill a circular through hole at the positions of the first electrode and the second electrode at a rotating speed of 18000 rpm and a feeding speed of 0.08 mm / s.

5. The manufacturing process of claim 2, wherein, The center distance between the two holes of the first electrode and the second electrode is 10.0 mm, and compressed air and isopropyl alcohol are used to clean the residues in the holes and around the holes after the drilling.

6. The manufacturing process of claim 5, wherein, The silver powder content of the conductive silver paste is 75wt% of the solderable silver paste, wherein the silver powder is mixed with flaky particles with an average particle size of 5 mu m and spherical nano-silver with an average particle size of 120 nm at a mass ratio of 6:4, and 0.3% of palladium elements are added as active additives. The printed conductive silver paste comprises:

7. The manufacturing process of claim 6, wherein, place the solderable silver paste in a planetary mixer, stir at a revolution speed of 300 rpm and a rotation speed of 900 rpm for 12 minutes, and then print the solderable silver paste into the electrode window area by using an 80-mesh stainless steel wire screen. The printed conductive silver paste further comprises:

8. The manufacturing process of claim 7, wherein, set the scraper angle to 65 DEG, apply a pressure of 0.45 MPa, and adopt a one-way double printing mode at a speed of 15 mm / s during printing, and stand for 3 minutes after each printing to obtain a pad structure with a total wet film thickness of 30 mu m. The printed conductive silver paste further comprises: send the printed polyimide film into a nitrogen protection oven with an oxygen content of less than 10 ppm, pre-bake at 80 DEG C for 8 minutes to remove the solvent, then heat at a rate of 4 DEG C / min to 180 DEG C and keep for 35 minutes to promote sintering and densification of the silver particles.

9. The manufacturing process of claim 8, wherein, The silver particles are sintered and densified, and then tin-lead eutectic solder heated to 220°C is applied to the electrode pads to observe whether it spreads rapidly to form a smooth solder joint with a contact angle of less than 45° within 0.5 seconds.

10. The manufacturing process of claim 2, wherein, A 35% solid content, 2500 cP viscosity acrylate protective coating is uniformly applied to the non-electrode area using a slot die, to a thickness of 12 μm, and then dried at 70°C for 10 minutes and allowed to cure at room temperature for 2 hours to complete the encapsulation.